2010
DOI: 10.1371/journal.pone.0011334
|View full text |Cite
|
Sign up to set email alerts
|

Outer Membrane Vesicles Derived from Escherichia coli Induce Systemic Inflammatory Response Syndrome

Abstract: Sepsis, characterized by a systemic inflammatory state that is usually related to Gram-negative bacterial infection, is a leading cause of death worldwide. Although the annual incidence of sepsis is still rising, the exact cause of Gram-negative bacteria-associated sepsis is not clear. Outer membrane vesicles (OMVs), constitutively secreted from Gram-negative bacteria, are nano-sized spherical bilayered proteolipids. Using a mouse model, we showed that intraperitoneal injection of OMVs derived from intestinal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

19
169
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 162 publications
(188 citation statements)
references
References 44 publications
19
169
0
Order By: Relevance
“…One study evaluating the involvement of molecules from Gram-negative bacteria in the promotion of sepsis showed that mice injected with outer membrane vesicles from Escherichia coli presented with clinically relevant symptoms, such as piloerection, eye exudates, hypothermia, tachypnea, leukopenia, hypotension and the systemic induction of tumour necrosis factor-alpha (TNF-α) and interleukin-6 (Park et al 2010). Pro-inflammatory cytokines, especially TNF-α, are associated with the development of cachexia (Silva et al 2001, Porto 2010.…”
Section: Discussionmentioning
confidence: 99%
“…One study evaluating the involvement of molecules from Gram-negative bacteria in the promotion of sepsis showed that mice injected with outer membrane vesicles from Escherichia coli presented with clinically relevant symptoms, such as piloerection, eye exudates, hypothermia, tachypnea, leukopenia, hypotension and the systemic induction of tumour necrosis factor-alpha (TNF-α) and interleukin-6 (Park et al 2010). Pro-inflammatory cytokines, especially TNF-α, are associated with the development of cachexia (Silva et al 2001, Porto 2010.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike the traditional, highly characterized type I to VI secretion systems, OMVs have the capacity to transport a mixture of soluble and insoluble material, which may be advantageous to the bacteria by protecting their cargo from proteases or by allowing for the assembly of multivalent complexes. Once released from bacteria, the vesicles are free to interact with the host, with considerable evidence that OMVs can be internalized into host cells (9,16,31) and have a role in modulating the host immune response (4,49,54,61).…”
mentioning
confidence: 99%
“…Gram-negative bacteria-derived EVs contain a wide variety of PAMPs, which can be capable of inducing innate immune responses and include LPS, outer membrane lipids, outer membrane proteins, periplasmic proteins, cytoplasmic proteins, DNA, RNA, and other virulence-associated factors (8,27). Our previous study demonstrated that the entry of E. coli EVs into the bloodstream induces systemic inflammation mimicking sepsis (10). In addition, our previous work indicates that EVs in indoor dust are important in the development of neutrophilic inflammation in the lung (11).…”
Section: Discussionmentioning
confidence: 99%
“…Our previous work has shown that E. coliderived EVs induce systemic inflammation mimicking sepsis after entering the bloodstream (10) and that EVs from indoor dust and also from Staphylococcus aureus can induce neutrophilic pulmonary inflammation (11,12). In the current study, we hypothesized that EVs from Gram-negative bacteria, especially E. coli, are an important cause of neutrophilic inflammation and thereby emphysema in the lung.…”
mentioning
confidence: 89%
See 1 more Smart Citation